IDENTIFICATION OF CHILDREN WITH SPECIAL NEEDS AT JUNIOR HIGH SCHOOL LEVEL DKI JAKARTA REGION - Marja (Universitas Negeri Jakarta, 2023)
This research is generally intended to obtain empirical data relating to the number of Children with Special Needs (ABK) at the junior high school level in the DKI Jakarta area in 2019. The research approach used in this study is a survey with a descriptive technique. The research subjects are junior high schools or public junior high schools in the DKI area which are taken in proportion to the number of 144 schools, which come from five regions. The data collection instrument is a questionnaire. As for the data analysis used descriptive statistical analysis techniques. The results of the research are the results of screening (identification) of ABK in DKI Jakarta with the most data on slow learners/slow learners with a total of 468 (45.44%), for the second most data, namely children with intellectual disabilities/mental retardation with a total of 230 (22.33). %), both types of ABK are related to intelligence barriers by having intelligence abilities below the normal average. This study shows that at the junior high school level in DKI Jakarta the number of students with below-normal intelligence abilities is quite high, both with slow learners and intellectual disabilities. Thus, this research has implications for the consolidation of concepts and practices in inclusive education services at the junior secondary level in DKI Jakarta. This research is also important, because the data regarding the number of crew members at the junior secondary level tend to be inadequate. This is expected to be a reference in increasing kites for ABK, especially in the setting of inclusive education services in DKI Jakarta.